2005
DOI: 10.1103/physreva.72.012333
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing entanglement by momentum jump in the frustrated Heisenberg ring at a quantum phase transition

Abstract: We study the pairwise concurrences, a measure of entanglement, of the ground states for the frustrated Heisenberg ring to explore the relation between entanglement and quantum phase transition associated with the momentum jump. The groundstate concurrences between any two sites are obtained analytically and numerically. It shows that the summation of all possible pairwise concurrences is an appropriate candidate to depict the phase transition. We also investigate the role that the momentum takes in the jump of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 23 publications
0
43
0
Order By: Relevance
“…State |n − , n + is the ground or first excited states of the whole system (the Hamiltonian (11) with g = 0), which are spanned by the states possessing the same parity as the states |n − , n + ; 0 = |n − , n + AB ⊗ |0 SSH . On the other hand, it is known that the eigenstates of H AB with unity concurrence are maximally entangled states [16,17]. Thus by calculating the mode concurrences of two sites A and B for the ground and first excited states of the total system (11), one can verify whether the exact solutions can be well approximated by that from the effective Hamiltonian.…”
Section: Reduced Density Matrix and Entanglementmentioning
confidence: 99%
“…State |n − , n + is the ground or first excited states of the whole system (the Hamiltonian (11) with g = 0), which are spanned by the states possessing the same parity as the states |n − , n + ; 0 = |n − , n + AB ⊗ |0 SSH . On the other hand, it is known that the eigenstates of H AB with unity concurrence are maximally entangled states [16,17]. Thus by calculating the mode concurrences of two sites A and B for the ground and first excited states of the total system (11), one can verify whether the exact solutions can be well approximated by that from the effective Hamiltonian.…”
Section: Reduced Density Matrix and Entanglementmentioning
confidence: 99%
“…An important issue is to understand how the structure of the ground state is affected by the existence of a critical point. The first answers came with the study of one-dimensional spin systems [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21] where a strong interplay between QPTs and the variation of the entanglement with the control parameters has been in evidence. However, a complete classification of the possible scenarios likely to arise depending on the nature of the transitions is still lacking [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It plays a fundamental role in quantum information processing (QIP) schemes and quantum computing, thus is regarded as an important resource for these technologies [1]. It also has been demonstrated that the quantum entanglement can be used to realize quantum teleportation [2,3,4,5], as well as to characterize the quantum critical phenomena in strongly correlated systems [6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%